Growth and hydrogen production of outdoor cultures of Synechocystis PCC 6803 - Touloupakis, Eleftherios (2016)
Synechocystis sp. PCC 6803, a freshwater cyanobacterium, was cultivated outdoors in a 50 L tubular photobioreactor to study the acclimation of cells to solar light in cultures grown at different initial mean biomass concentrations (1.10, 0.60, and 0.32 g L− 1). Chlorophyll fluorescence quenching analysis, coupled with measurements of photosynthesis and respiration rates, showed that photoinhibition strongly affected the performance of the culture grown at lowest biomass concentration (0.32 g L− 1). In this culture the Fv/Fm ratio at noon declined to one fourth compared to the morning, and no recovery occurred in the afternoon. Optimal biomass concentration for growth was 0.60 g L− 1 which resulted in a biomass yield of 24.6 g m− 2 day− 1. The ability of the cells to produce hydrogen via an indirect light driven process was investigated both in the laboratory and in the outdoor photobioreactor. The rate of hydrogen production achieved in the laboratory reached 3.07 mL H2 L− 1 h− 1 (i.e., 6.55 μmol H2 mg Chl− 1 h− 1) while that attained in the 50 L photobioreactor was 0.05 mL H2 L− 1 h− 1 (0.39 μmol H2 mg Chl− 1 h− 1). The production of hydrogen in the dark was sustained by fermentation of carbohydrates accumulated during the nitrogen starvation of cells under the light.